iPSC‐based modeling of THD recapitulates disease phenotypes and reveals neuronal malformation - Alba Tristán‐Noguero; Irene Fernández‐Carasa; Carles Calatayud; Cristina Bermejo‐Casadesús; Meritxell Pons‐Espinal; Arianna Colini Baldeschi; Leticia Campa; Francesc Artigas; Analia Bortolozzi; Rosario Domingo‐Jiménez; Salvador Ibáñez; Mercè Pineda; et al. (EMBO Molecular Medicine)
Abstract Tyrosine hydroxylase deficiency (THD) is a rare genetic disorder leading to dopaminergic depletion and early‐onset Parkinsonism. Affected children present with either a severe form that does not respond to L‐Dopa treatment (THD‐B) or a milder L‐Dopa responsive form (THD‐A). We generated induced pluripotent stem cells (iPSCs) from THD patients that were differentiated into dopaminergic neurons (DAn) and compared with control‐DAn from healthy individuals and gene‐corrected isogenic controls. Consistent with patients, THD iPSC‐DAn displayed lower levels of DA metabolites and reduced TH expression, when compared to controls. Moreover, THD iPSC‐DAn showed abnormal morphology, including reduced total neurite length and neurite arborization defects, which were not evident in DAn differentiated from control‐iPSC. Treatment of THD‐iPSC‐DAn with L‐Dopa rescued the neuronal defects and disease phenotype only in THDA‐DAn. Interestingly, L‐Dopa treatment at the stage of neuronal precursors could prevent the alterations in THDB‐iPSC‐DAn, thus suggesting the existence of a critical developmental window in THD. Our iPSC‐based model recapitulates THD disease phenotypes and response to treatment, representing a promising tool for investigating pathogenic mechanisms, drug screening, and personalized management.